SCIENCE AND ITS SOCIETY ROLE IN DEVELOPMENT - Usmanov Murad Sadigovich (Galaxy International Interdisciplinary Research Journal, 2022)
It is known that at all stages of the development of society, the development of Science and technology of that time, as well as the regular consumption of their results, played an important role, and even sometimes, they took place in the revolutionary nature of the development of Science and technology. About this we are witnesses of the” Stone Age“,” Bronze Age“, ”transformation of energy from one species to another“, ”Atomic Age“,” Age towards an informed society“,” intellectual age " and visible evidence.